Unity Android 2021 : build 3D ZigZag racing game with C#. (Packt Publishing, 2022)
Master the basic concepts, tools, and functions required to build fully functional Android mobile games with the Unity game engine. About This Video Learn to play ads less frequently with ad counter Learn C# scripting basics for absolute beginners Learn the tricks to build an Android game in 15 minutes and in an hour In Detail Learning the fundamentals of Unity Android game development puts a powerful and particularly useful tool at your fingertips. Unity is free, easy to learn, has excellent documentation, and is the game engine used for building Android games. Jobs in Unity Android game development are plentiful and being able to learn it will give you a strong background to easily build awesome Android games. Starting with the installation of Unity, Java Development Kit, and Android SDK, this course will take you through various Unity features and how to use them. By creating example games, you will establish a strong understanding of Unity game development. With these basics mastered, the course will take you through building different example games with Unity to learn more about the process of creating mobile Android games with Unity. By the end of the course, you will have the knowledge to create fully functional and ready to publish Android games with Unity. Audience This course is for anyone willing to learn how to build and publish Android games with Unity. Basic understanding of Unity and C# is an added advantage.